Factors Influencing the Utilization of Skilled Delivery Service in Kasoa, in the Awutu Senya-East Municipality. - Nelson, P.R. (University of Ghana., 2019)
Background: The complication that comes with pregnancy and delivery are enormous. The success of the pregnancy and the aversion of the complication depends on level at which the pregnant woman utilizes skilled delivery. Unfortunately, the utilization of skilled delivery services in Sub-Saharan Africa and Ghana has been low over the years with many women delivering at Home under the supervision of Traditional Birth Attendants (TBAs). Several factors such as poor knowledge, Luck of funds, level of education, community constraints, health providers’ attitude etc. were identified as influencing the utilization of skilled delivery services in Ghana and other parts of Africa. These challenges are likely to be similar to what is happening at Kasoa, in the Awutu Senya Municipality. This study therefore aims at identifying the factors influencing the utilization of skilled delivery services in Kasoa. Method: A cross-sectional study using structured questionnaires was used to collect information on 406 women or the reproductive age (15-49) who had delivered in period of one year prior to the study in ten (10) communities in Kasoa. Names of the communities were written on papers and ten communities were picked at random. A pen was thrown into the air and allowed to fall back to the ground at the centre of each community to enable participants choose the immediate house in the direction of the head of the pen. Balloting was done to recruit participants in homes that had more than one potential respondent. Data collected were coded and entered into Excel 2016 and was cross-checked and validated to correct all errors. The data was then exported to STATA version 15 for analysis. Univariate analysis was conducted and the results were presented as frequencies, percentages, figures and tables. Bivariate analysis and logistics regression modeling were done to determine association between background characteristics of respondents and the uptake of skilled delivery services. Results: Out of 406 respondents, 385(94.8%) were found to have skilled delivery service. Most of the mothers who utilized the services were aged 20-29 years representing 46.6% with the least being those above 40 years (6.4%) followed by the adolescent (7.6%). Only 38 (9.4%) of them did not have any formal education. The major factors identified as influencing utilization of skilled delivery were education, financial status, support of partners and place of residence and choice of work of partner. Conclusion: the results show that, utilization of skilled delivery services in Kasoa is high among the mothers and this is influenced by factors such as education, place of residence, support of partners, finance etc.
MA. Public Health
Keywords: Skilled Delivery; Factors Influencing the Utilization of Skilled Delivery; Awutu Senya-East; Pregnancy; Complications